Multiscale inorganic hierarchically materials: towards an improved orthopaedic regenerative medicine - Ruso, Juan Manuel (2015)
Bone is a biologically and structurally complex multifunctional tissue. It dynamically responds to biochemical, mechanical and electrical signals by remodelling itself so that maximum strength and toughness are along the lines of the greatest applied stress. The challenge is to develop an orthopaedic biomaterial that emulates the micro- and nano-structural elements and compositions of bone to locally match the properties of the host tissue resulting in a biologically fixed implant. Looking for the ideal implant, the convergence of life and materials sciences occurs. Researchers in many different fields apply their expertise to improve implantable devices and regenerative medicine. Materials of all kinds, but especially hierarchical nano-materials, are being exploited. The application of nano-materials with hierarchical design to calcified tissue reconstructive medicine involve intricate systems including scaffolds with multifaceted shapes that provides temporary mechanical function; materials with nano-topography modifications that guarantee their integration to tissues and that possesses functionalized surfaces to deliver biologic factors to stimulate tissue growth in a controlled, safe, and rapid manner. Also materials that should degrade on a timeline matched to the time it takes to grow tissues are prepared. These implantable device systems are multifunctional and require specific design techniques coupled with several material manufacturing processes that can be integrated to achieve the design that can address the required multifunctionality. For such reasons, even though the concept shift from synthetic implants and tissue grafts to regenerative-medicine-based tissue reconstruction has been assured for well over a decade, the reality has yet to emerge. In this paper, we review the recent approaches to create enhanced bioactive materials. Their design and manufacturing processes as well as the challenges to integrate them to engineer hierarchical inorganic materials for their practical application in calcified tissue reparation are evaluated.